Thermal and gas characteristics of large-format LiNi0.8Co0.1Mn0.1O2 pouch power cell during thermal runaway. (July 2021) - Zou, Kaiyu; Lu, Shouxiang; Chen, Xiao; Gao, Erping; Cao, Yong; Bi, Yubo
Highlights: Applicability of thermal evaluation of large-format pouch cell in EV+ARC. Multi-point measurement was used to visualize the temperature distribution. Heat production was calculated by the distributed parameter method. Abstract: With the widespread use of lithium-ion batteries as a power source, higher and higher energy density has been required. This study focused on a promising battery with representative high energy density. The thermal and gas characteristics of large-format LiNi0.8 Co0.1 Mn0.1 O2 pouch power cell during thermal runaway were investigated using Extended Volume+ Accelerating Rate Calorimetry (EV+ ARC). Differing from previous studies, the characterization of large-format pouch cells cannot be studied by the lumped parameter method, while the multi-point measurement was adopted to visualize the variation of temperature distribution. The calorimetry that has been commonly used for evaluating thermal runaway of batteries was discussed whether it is also applicable to the large-format pouch cell. And the distributed parameter method was utilized to explore the heat production of the large-format cell. Also, the gas generated by the thermal runaway cell was analyzed by gas chromatography, and the gas generation mechanism of the LiNi0.8 Co0.1 Mn0.1 O2 cell was traced based on the results. This work also confirmed the thermal runaway hazard of LiNi0.8 Co0.1 Mn0.1 O2 pouch power cell and could provide a reference for the evaluation of thermal runaway and application safety of large-format batteries.